(untitled) (Indian Journal of Animal Production and Management, 2016)
The present investigation was aimed to study the constraints faced by women dairy farmers in cooperative society related to dairy farming. The study was purposively carried out at MWCD (Mulukanoor Women Dairy Cooperative) in Karimnagar district of Telangana state as the same has much influence on women empowerment through cooperatives. The results found on perceived constraints among member and non member groups revealed that, inadequate irrigation and small land holding for green fodder cultivation and Non availability of purebreds and lack of awareness about hay and silage making, pricing policy and Non availability of chaff cutters were found to be the major constrains among member and non-member groups, respectively and these constraints could be attributed to financial constraints among members and lack of awareness among non-member groups of women.